Supressor tumoral ABI3 (ABI family member 3): desvendando os mecanismos moleculares nos tumores da tiroide humana - Moraes, Lais de Sousa [UNIFESP] (2016)
We identified the loss of ABI3 gene expression in thyroid carcinomas. Functional analysis demonstrated that ectopic expression of ABI3 inhibits cell growth, invasion, migration and tumor growth in vivo associated with an increased in cellular senescence, suggesting ABI3 as a potential tumor suppressor. Nevertheless, there is no genetic/ epigenetic mechanisms described as associated with its loss of expression, and it is still unknown the signaling pathway by which ABI3 exerts its function. Based on these data about ABI3, our first objective was to investigate if DNA methylation could be the mechanism responsible for the loss of ABI3 expression in follicular thyroid carcinoma (FTC). The cell lines derived from follicular thyroid carcinoma (WRO, FTC 238, and FTC236 FTC133) and melanoma (NPA) were treated with demethylating agent (5-Aza) and the level of ABI3 expression was assessed. We observed the restoration of ABI3 expression in follicular carcinoma cell lines treated with 5-Aza (P<0.01). Thus, we correlated the level of ABI3 expression with degree of methylation of its promoter. Although the in silico analysis showed that ABI3 has no CpG islands, we identify the occurrence of multiple adjacent CpG sites in its promoter. These regions called R1, R2 and R3 were evaluated. The degree of methylation of R1 region was inversely correlated with ABI3 expression in these cells (P<0.05). These data were validated on FTC (n=17) and follicular thyroid adenomas (FTA) (n=11) samples. We observed a hypermethylation of R1 in CFT when compared to the AFT (P<0.001), which correlated with the expression of ABI3 (P=0.0002). Interestingly, we identified in R1 a canonical site for the thyroid transcription factor NKX2-1, flanked by the CpG sites. The analysis revealed that ABI3 was expressed in the presence of NKX2-1 and when R1 region is hipomethylated. Luciferase assays suggested that R1 might be a potential enhancer. Our data suggest that ABI3 expression in thyroid tumors appears to be regulated by R1 methylation degree in ABI3 promoter associated with expression of NKX2-1. Yet, to better understand the molecular mechanisms involved in the role of ABI3 in thyroid cancer, our second objective was to investigate the signaling pathways by which ABI3 acts exercising their suppressive effect in thyroid carcinomas. To this end, the follicular thyroid carcinoma cell lines, WRO and FTC133 were transfected with the expression vector containing the wild type cDNA of ABI3 and negative control, the empty vector. Initially, we used the Proteome Profiler Array to identify the signaling pathways, and some pathways described as having been a role in several types of cancer were identified as modulated by ABI3, particularly AKT pathway was enriched in our analysis. To better determine the location of the ABI3 in the signaling pathway, we performed immunoprecipitation assays (IP) and mass spectrometry analysis that showed ABI3 as a part of the WAVE regulatory complex (WRC) with WAVE2 and CYFIP1 proteins. To validate these data, the cells lines were treated with AKT inhibitor (LY294002). In addition, the ABI3 S342A mutant was generated by site-directed mutagenesis. The determination of S342 site was performed by in silico analysis with MotifScan. For the first time, our studies with AKT inhibitor and S342A mimetic mutant of non-phosphorylated form of ABI3 demonstrated that ABI3 is a phosphoprotein, directly phosphorylated by AKT in S432. And this phosphorylation probably interferes with the formation of the WRC complex. The results were observed in both cell lines and the correlation between ABI3, WAVE2 and CYFIP1 was validated in samples of patients (n=23) that expressed ABI3, FTA and normal thyroid tissue (P<0.05). These data are new in the literature and suggests a relationship between the ABI3 phosphorylation, AKT and the formation of WRC complex. Furthermore, these data suggest a possible pathway by which ABI3 acts exerting its suppressive effects, particularly their effects on cell growth and migration.